Penerapan Model Pembelajaran Kooperatif Time Token Untuk Meningkatkan Kemampuan Berbicara Bahasa Arab Pada Peserta Didik - Nurjannah Nurjannah (Dinasti Research, 2022)
Learning Arabic at MTsN 10 Bireuen, especially in class IX.1 is still low, especially in Arabic speaking skills, because learning Arabic in class IX.1 they have not used effective and interesting strategies, learning models, and learning media so that they can attract students' interest in learning to speak Arabic. One effort as an alternative solution to this problem is to apply the cooperative learning time token learning model to support students in the process of learning Arabic speaking skills. This research is a Classroom Action Research (CAR) with the aim of knowing the effectiveness of the Time Token type Cooperative Learning learning model to improve the Arabic speaking skills of class IX.1 MTsN 10 Bireuen academic year 2022/2023. The results of this study indicate an increase in the average score on the test. In the first cycle 73.65 and in the second cycle 79.85.